Impact of anti-interleukin-6 receptor blockade on circulating T and B cell subsets in patients with systemic lupus erythematosus. Issue 1 (2nd August 2012) - Shirota, Yuko; Yarboro, Cheryl; Fischer, Randy; Pham, Tuyet-Hang; Lipsky, Peter; Illei, Gabor G
Abstract : Background: Circulating plasmablasts/plasma cells and activated B and T cells are increased in systemic lupus erythematosus (SLE). Interleukin (IL)-6 induces differentiation of B cells into antibody-forming cells and of T cells into effector cells. Objective: To examine the hypothesis that blocking IL-6 would reverse some of the immune abnormalities present in SLE. Methods: Fifteen patients with SLE with mild-to moderate disease activity were treated with biweekly infusions of tocilizumab, a humanised anti-IL-6 receptor monoclonal antibody for 12 weeks. Lymphocyte subsets (analysed by flow cytometry) and serum immunoglobulin levels were compared at baseline and at weeks 6 and 12. Results: Tocilizumab decreased activated T and B cells, the frequency of CD27 high CD38 high IgD− plasmablasts/plasma cells and IgD−CD27+ post-switched memory B cells as well as IgG+ memory B cell, whereas it increased the frequency of IgD+CD27− antigen-inexperienced B cells. Among antigen-inexperienced IgD+CD27− B cells, CD38 low mature naïve B cells increased significantly and CD38 Intermediate CD5+ pre-naïve B cells showed a decreasing trend, whereas CD38 high CD5+ transitional type 1 B cells did not change. Most of the changes occurred in patients who had abnormal values at baseline. IgG, IgA, IgG1 and IgG3 serum levels decreased albeit within the normal range. The frequency of CD4+CD45RA+CCR7+ naïve T cells increased. Conclusions: In vivo blockade of the IL-6 receptor decreases lymphocyte activation and restores B and T cell homoeostasis by either blocking differentiation and/or trafficking in patients with SLE and leads to normalisation of the abnormal B and T cell subsets seen at baseline.